An evaluation of creep rupture strength of ferritic/austenitic dissimilar weld interfaces using cohesive zone modelling - Hu, J; Fukahori, T; Igari, T; Chuman, Y; Cocks, ACF (Elsevier, 2016)
Dissimilar metal welds between ferritic and austenitic alloys are used extensively in power generation plants. Failure of such welds can occur in the base metal, the heat-affected zone (HAZ), or the interface between the two materials, depending on the operating stress and temperature. Evaluation of the creep rupture properties of dissimilar weld joints of 2.25Cr-1Mo (P22) and 9Cr-1MoVNb (P91) ferritic steels with INCONEL 82 filler metal are described, with the primary focus on failure at the interface. The interface is modelled as a cohesive, or interface, zone within a finite element (FE) analysis. A Kachanov-type damage accumulation law is implemented to describe the response within the interface element, with the material parameters calibrated against available experimental data. The relationship between the damage mechanics model and the major microstructural features that are responsible for failure, is discussed.